Accuracy of predicted haemoglobin concentration on cardiopulmonary bypass in paediatric cardiac surgery: effect of different formulae for estimating patient blood volume. (November 2017) - Redlin, Matthias; Boettcher, Wolfgang; Dehmel, Frank; Cho, Mi-Young; Kukucka, Marian; Habazettl, Helmut
Introduction: When applying a blood-conserving approach in paediatric cardiac surgery with the aim of reducing the transfusion of homologous blood products, the decision to use blood or blood-free priming of the cardiopulmonary bypass (CPB) circuit is often based on the predicted haemoglobin concentration (Hb) as derived from the pre-CPB Hb, the prime volume and the estimated blood volume. We assessed the accuracy of this approach and whether it may be improved by using more sophisticated methods of estimating the blood volume. Patients and Methods: Data from 522 paediatric cardiac surgery patients treated with CPB with blood-free priming in a 2-year period from May 2013 to May 2015 were collected. Inclusion criteria were body weight <15 kg and available Hb data immediately prior to and after the onset of CPB. The Hb on CPB was predicted according to Fick's principle from the pre-CPB Hb, the prime volume and the patient blood volume. Linear regression analyses and Bland-Altman plots were used to assess the accuracy of the Hb prediction. Different methods to estimate the blood volume were assessed and compared. Results: The initial Hb on CPB correlated well with the predicted Hb (R 2 =0.87, p<0.001). A Bland-Altman plot revealed little bias at 0.07 g/dL and an area of agreement from -1.35 to 1.48 g/dL. More sophisticated methods of estimating blood volume from lean body mass did not improve the Hb prediction, but rather increased bias. Conclusion: Hb prediction is reasonably accurate, with the best result obtained with the simplest method of estimating the blood volume at 80 mL/kg body weight. When deciding for or against blood-free priming, caution is necessary when the predicted Hb lies in a range of ± 2 g/dL around the transfusion trigger.